Coordinated cadastral system for Peninsular Malaysia : from concept to reality - A. Kadir, Abd. Majid; Omar, Abdullah Hisam (2005)
The main objectives of conducting cadastral surveys that had been promulgated in the early days of its practice have since been continually adhered to and later came to be adopted as amongst the principal functions of DSMM. They were stated in the Survey Regulations (DSMM, 1976) as follows: “(a) To provide evidence which will completely and permanently identify the land conveyed by any title issued by government. (b) To compile and make available records of alienation necessary for intelligent land administration.”